Efektivitas Pengelolaan Zakat Nasional: Analisis Dampak Pendistribusian Zakat Terhadap Keadilan Sosial di Indonesia - Prambudhi, Yudho; Ribawati, Eko (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
This study discusses the effectiveness of national zakat management in addressing social inequality and promoting equitable welfare distribution in Indonesia. The research is based on the fact that the optimization of zakat distribution remains low, despite the continuous increase in national zakat potential each year. The purpose of this study is to analyze the extent to which national zakat management supports social justice, to examine its contribution as an Islamic economic instrument aligned with the values of Pancasila, and to identify the factors that support and hinder its effectiveness. This research employs a qualitative method with a descriptive-analytical approach, using secondary data sources such as annual BAZNAS reports, BPS publications, government regulations, and related academic literature. The findings indicate that the effectiveness of national zakat management is supported by strong regulations, government involvement, technological innovation, and increasing public awareness. However, its implementation still faces challenges such as low zakat literacy, lack of synergy among zakat institutions, limited human resources, and insufficient data integration. Therefore, optimizing zakat management requires enhancing literacy, strengthening institutional collaboration, and advancing digitalization to reinforce the role of zakat in achieving social justice in Indonesia.